2012
DOI: 10.1177/0095399712451887
|View full text |Cite
|
Sign up to set email alerts
|

Context and Nonprofit Human Resource Management

Abstract: The article presents a framework of nonprofit human resource management (NHRM) that emphasizes the context of nonprofits, organizational and employee characteristics. Drawing on contingency theory and social exchange theory, the article examines the multidimensional contingencies in the environment of nonprofit organizations and the characteristics of employees that underlie NHRM. Three underlying principles and five models of NHRM are presented to explain the dimensions of NHRM. The concept of social alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 97 publications
1
27
0
Order By: Relevance
“…Internally, the context of the organization, its environment, mission, and staff characteristics determine personnel policies and procedures that will be effective in supporting the staff (Akingbola, 2012). Wilensky and Hansen (2001 ), found that nonprofit leadership considered some of the most important aspects of their job was to motivate staff within the context of the mission and to keep the organization on track, especially through organizational change.…”
Section: Nonprofit Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internally, the context of the organization, its environment, mission, and staff characteristics determine personnel policies and procedures that will be effective in supporting the staff (Akingbola, 2012). Wilensky and Hansen (2001 ), found that nonprofit leadership considered some of the most important aspects of their job was to motivate staff within the context of the mission and to keep the organization on track, especially through organizational change.…”
Section: Nonprofit Organizationsmentioning
confidence: 99%
“…Further support of the idea that nonprofit employees' relationship to their organizations may be different than their counterparts in other sectors is Akingbola's (2012) nested social exchange model designed to explain the exchange or relationship between employees and their organizations. He nests both the economic exchange and social exchange in a third level derived from the social objectives, values and environment of the nonprofit organization (p. 984).…”
Section: Organizational Citizenship Behavior (Ocb) Organizational CImentioning
confidence: 99%
“…Law or regulation impose some management practices: hospital administrators have little choice of whether hospital volunteers will be afforded liability coverage. However, where strategic decision‐making is concerned, the universalistic hypothesis contradicts a half‐century of structural contingency theory, which suggests that performance dictates when organizations should adopt the strategies that fit their task environment and structure (Akingbola ; Drazin and Van de Ven ). It also stands in contrast with prevailing conceptions of strategic human resource management theory that observe patterns of adoption related to environmental conditions and internal consistency (Ketchen, Thomas, and Snow ; MacDuffie ).…”
Section: Universalistic Versus Contingent or Configurational Adoptionmentioning
confidence: 99%
“…Many strategies employed by for-profit Human Resources team have been applied to non-profit organizations, showing a clear intention from the management, donors, and stakeholders to create accountability within the organizations (Akingbola, 2006;Taylor & McGraw, 2006;Hunter & Ranwick, 2009;Akingbola, 2013;Ridder, Baluch, & Piening , 2012).…”
mentioning
confidence: 99%